The Implications of Sigmund Freud’s Psychoanalytic Theory in Educational Philosophy for the Development of Character Education in Indonesia: - Yulika Gita Rahayu Ningtyas; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
Character education in Indonesia is currently at a turning point due to students’ deviant behavior and moral deterioration. This phenomena necessitates a deeper theoretical understanding of the nature of the human psyche in order to build meaningful character. This study aims to explore how Sigmund Freud’s psychoanalytic theory has evolved within the framework of educational philosophy and how it has improved character education in Indonesia. This study used a qualitative descriptive method through library research. An examination of primary and secondary sources created between 2022 and 2026 was done to make sure the data was pertinent to the current educational setting. The findings suggest that the dynamics of the Id, Ego, and Superego personality structures have a major role in determining moral behavior. The key to developing a character with integrity is to strengthen the superego by internalizing moral principles at a young age. Freud’s psychoanalytic theory offers an axiological and epistemological basis for the creation of a character-based curriculum from the standpoint of educational philosophy. This suggests the necessity of an educational strategy that targets students’ subconscious, emotional, and psychological qualities in addition to their cognitive abilities. From a philosophical standpoint, psychoanalysis provides “consciousness-based education,” emphasizing emotional equilibrium with an axiological and epistemological basis. Indonesian character education needs to reform. Formal-legalistic tactics have been substituted with psychological-persuasive techniques that take the subconscious into account. Education must be able to sustain students’ egos in order for them to rationally and healthily moderate moral demands.